EFEK EKSTRAK TESTIS TERHADAP JUMLAH IMPLANTASI DAN JUMLAH ANAK PADA MENCIT (Mus musculus) - Sri Puji Astuti Wahyuningsih; Listijani Suhargo; Kushendarsasi (The East Java Biological Society, 2004)
Extract of testis contains the testis specific proteins. The testis proteins may raise immune responses. The immune responses are the antibodies against testis specific anti-protein. The reaction between the antibodies and the sperms can inhibit fertilization. This process has contraception effects. This research used 24 female and 20 male mice strain Balb/c. The experiment used the complete random design with 4 concentration treatments (0, 500, 1000, and 2000 μg extracts of testis) and 3 replications. Mice were injected 3 times with time interval 21 days. After 15 days from the rising of vaginal plug, 3 mice were dissected and counted the implantation. The others mice were waited until delivered of the children. The datas were analyzed by ANOVA and LSD (α = 5%). The results showed that extract of testis did not influence the amount of implantation at the uterus endometrial, but it decreased the amount of children. The effective concentration of extract testis is 2000 μg. So, this study showed that the intraperitoneum injection of the extract of testis had contraception effects.